1997
DOI: 10.1119/1.18729
|View full text |Cite
|
Sign up to set email alerts
|

Finding the surface temperature of the Sun using a parked car

Abstract: A preliminary analysis of dynamic and realistic heliosphere using interplanetary scintillation and photospheric magnetic data AIP Conf.We present an activity, involving a parked car, for estimating the surface temperature of the Sun. The activity entails both outdoor quantitative observations and theoretical analysis, and yields a result for the surface temperature of the Sun within 12% of the accepted value. It can be used as an independent study project to spark students' interest and facilitate learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In many settings with challenging topics, the use of astronomy or astronomy-related activities has shown to significantly help high-school and college students grasp complex concepts and help them get into science [13,18]. Furthermore, several researchers have shown that evidence-based active engagement courses help students significantly to grasp complex concepts [15,24], and even reduce the gender gap in STEM areas [14]. This improvement is further enhanced by making students use real data and even capture the data themselves [2,9].…”
Section: Introductionmentioning
confidence: 99%
“…In many settings with challenging topics, the use of astronomy or astronomy-related activities has shown to significantly help high-school and college students grasp complex concepts and help them get into science [13,18]. Furthermore, several researchers have shown that evidence-based active engagement courses help students significantly to grasp complex concepts [15,24], and even reduce the gender gap in STEM areas [14]. This improvement is further enhanced by making students use real data and even capture the data themselves [2,9].…”
Section: Introductionmentioning
confidence: 99%